The efficacy of virtual counseling on the mothers’ knowledge about baby massage during COVID-19 pandemic - Neny Octavia Hidayat; Dyah Noviawati Setya Arum; Nur Djanah (Jurnal Kesehatan Ibu dan Anak, 2022)
Early stimulation in form of massage for babies for 0-6 months old can strong then the bond and develop the sense of secure between babies and their mothers.  Covid-19 pandemic forces for learning and education to be done through online classes including health promotion, in this case baby massage. The aim of study was to find out the average difference on mothers' increase of knowledge about baby massage before and after virtual counseling during Covid 19 pandemic. This was experimental research using quasi experiment design with non-randomized pre and posttest with control group design approach that was conducted on November   2021 in Sleman, Yogyakarta. The population of this research are mothers who have babies in the age of 0-6 months. The sampling technique used simple random sampling on 126 respondents, 63 respondents as the control group and 63 respondents as the experiment group. The experiment group was given virtual counseling through zoom cloud meeting, while the control group was given counseling using power point presentation through WhatsApp group. The data analysis used Wilcoxon and Mann Whitney test. The tool that was used was questionnaire through google form. There was an increase on the knowledge between the two groups with p-value=0.001. Virtual counseling was effective on the increase of mothers’ knowledge on baby massage during the covid-19 pandemic.